The Influence of Reading Habit on Students’ Writing Skills among EFL Learners - Edwina Letare; Sanggam Siahaan (The Future of Education Journal, 2026)
Reading habit is widely recognized as an important factor that contributes to students’ language development, particularly in improving writing skills among English as a Foreign Language (EFL) learners. This study aims to investigate the influence of reading habits on students’ writing skills through a review of previous studies. The study employed a library research design by analyzing findings from 25 relevant studies related to reading habits and writing skills in EFL contexts. The data were collected from academic journals, research articles, and scholarly publications and were analyzed qualitatively through identification, comparison, interpretation, and synthesis of the findings. The results reveal that reading habit has a positive influence on students’ writing skills. Students who engage in regular reading activities tend to demonstrate better writing ability, richer vocabulary knowledge, stronger idea development, improved understanding of grammatical structures, and better organization of written texts. The findings also indicate that reading provides learners with valuable language input and knowledge that support the writing process. Furthermore, students with strong reading habits generally show greater confidence and competence in expressing their ideas through writing. Although the reviewed studies focus on different aspects of writing development, they consistently emphasize the significant role of reading in enhancing writing performance among EFL learners. Therefore, it can be concluded that fostering regular reading habits is an effective strategy for improving students’ writing skills and supporting their overall English language proficiency. The findings of this study may serve as a reference for teachers, students, and researchers in promoting reading as a means of developing writing competence.